(untitled) (Global Journal of Sciences, 2024)
While COVID-19 is no longer the main public health challenge, we should still exercise caution. The rapid spread of the virus in the past presented a significant threat to public health, highlighting the need for continued vigilance and effective preventive measures. Over the years, science-related groups, institutions, healthcare services, schools and companies have collaborated in finding a common remedy to contain the virus. Therefore, there is a need of using safer products to disinfect or prevent the presence of the virus in our environs.